Knowledge, attitudes, and practices of cigarette smokers on third hand smoke and its potential effect on smoking cessation - Abiog, Markus L.; Castalone, Alfonzo Q.​; Mamaradlo, Giana Leigh D.​ (College of Pharmacy, University of the Philippines, 2019)
Smoking remains one of the most preventable risk factor for diseases such as cancer and cardiovascular diseases. Not only does it negatively affect smokers but also others around them through passive smoking. Third hand smoke is a type of passive smoke and is defined as the tobacco residues that mix with the air and dust and adhere to surfaces. Evidences suggests that exposure to it may cause serious health risks. This study aimed to determine the association of knowledge, attitudes, practices (KAP) towards third hand smoke with intent to undergo smoking cessation in cigarette smokers. A total of 395 smokers were included in this study. Data was collected through a survey questionnaire that assessed their knowledge, attitudes and practices towards third hand smoke, and their level of intent to undergo smoking cessation. Chi-square analysis and Fisher's exact test were applied to determine association between variables. It was determined that neither knowledge, attitudes, or practices had a significant association with intent to undergo smoking. This may be attributed to the demographic factors of the population that may have affected one's intent, specifically: having started smoking before the age of 18, being employed, having low socioeconomic status, having reached only up to high school, and currently living with other active smokers. Further analysis revealed that demographic factors also showed no significant associations with the intent to undergo smoking cessation. The findings of this study may be used towards improving smoking cessation programs in the country.